Trust in Local Governments: An Insight for Good Governance Practices in COVID-19 Management - Burhanudin Burhanudin; Muhammad Reza Fahlevy; Muhammad Fitrah (Universitas Pendidikan Ganesha, 2022)
Various countries from almost all corners of the world and international organizations involved in providing development assistance have actively implemented and encouraged a paradigm shift in governance and development based on good governance. This study examines public trust in implementing good governance in terms of accountability, responsiveness, transparency, and information technology of the Samarinda City government in dealing with the COVID-19 pandemic. The research method used in this research is qualitative. Data collection in this study prioritized in-depth interviews with twenty questions posed to six informants from the general public and six from the Samarinda City Government. The data analysis approach in this study uses the Nvivo 12 Plus software, and the processing uses the Crosstab Query Analysis functionality. The results of this study indicate that the practice of accountability, responsiveness, transparency, and information technology of the Samarinda City government varies greatly. In terms of responsibility, very good. Then, information technology in Samarinda City is quite good. Meanwhile, in terms of responsiveness and transparency, it still does not provide maximum results. Public trust in the government in handling COVID-19 has various perspectives based on findings from the implementation of good governance.